Beyond the black box: Digital media players as interoperable systems - Baumann, Chris (Journal of Popular Television, The, 2019)
This article looks at the entanglement of materiality, social practices and institutional interventions connected to the emergence of digital media players, in order to understand the cultural practices that their development and stabilization provoke. After laying out a framework for studying interconnectivity in complex systems, and introducing the notion of interoperable systems as a conceptual intervention for the study of media technologies, I offer a case study of the development of Microsoft’s Xbox One, in which particular attention is paid to the various ‘repair practices’ that the system’s limitations motivated among different social groups. I argue that seemingly ‘simple’ and ‘seamless’ operations that an everyday phenomenon like the Xbox One promises, such as using the device to stream a video, are in fact made possible by a complex set of technological, social and organizational mechanisms that are deliberately negotiated and manipulated at different layers.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qcHR2LjcuMi4yMDFfMQ